Clinical assessment of nutritional status among school going children aged 6-15 years in tea garden area of Darjeeling district, West Bengal, India - Baidya, Debangshu; Ghosh, Biswajit; Karmakar, Balai Chandra (International Journal of Contemporary Pediatrics, 2024)
Background: Malnutrition (undernutrition) is a spectrum of disorder caused by various intervening factors which results in formation of ‘web of causation’ and prevalence is very high in developing countries like India which may lead to deficient physical growth as well as suboptimal mental achievement. The present study was designed to assess the nutritional status among school going children in remote tea garden area of Darjeeling district by clinical assessment. Methods: This cross-sectional study was conducted among 768 students covering both, the hilly areas and plains of Darjeeling district, and recommended anthropometric parameters and indices of world health organization (WHO) were applied. The data was compiled with MS excel and suitable statistical test were done using SPSS version 20.0 software. Results: Out of 768 school going children aged between 6-15 years, wasting was prevalent among 13% with 1% prevalence of severe wasting, thinness was prevalent among 40%, 25% students suffered from stunting, with 4.6% prevalence of severe stunting. The study revealed a statistically significant (p<0.05) difference of mean weight between boys and girls belonging to age groups of 6+ years, 7+ years, 8+ years and 13+ years, and also of mean height of the boys and girls belonging to the age groups of 6+, 7+, 8+, 13+ and 14+ years. Pallor was also prevalent among 30.5% of the children. Conclusion: Malnutrition was common among the school age children of Darjeeling district in the age group of 6-15 years.